The Effect of Patellar Surface Morphology on Subchondral Bone Alignment When Matching Patellar Osteochondral Allografts to the Central Ridge of the Patella. Issue 6 (May 2022) - Neral, Mithun; Patel, Karan A.; Getty, Michael; Salka, Nabeel; Grant, John A.
Background: Cartilage transplants in the patellofemoral joint have demonstrated lower success rates than in the femoral condyles. This is likely related to the more complex morphology and biomechanics of the joint. While previous studies have evaluated cartilage surface matching and congruence, little work has been done to study the associated subchondral bone congruency in these grafts. Purpose: To determine if differences in patellar morphology play a role in the alignment of the donor patellar osteochondral allograft subchondral bone with the native patellar subchondral bone. Study Design: Controlled laboratory study. Methods: A total of 20 (10 Wiberg I and 10 Wiberg II/III) fresh-frozen human patellae were designated as recipients and size-matched to both a Wiberg I and a Wiberg II/III patellar donor. A 16-mm osteochondral allograft transplant to the central ridge of the patella was performed in random order with each matched donor. Transplanted patellae underwent a nano—computed tomography (nano-CT) scan, were digitally reconstructed, and were superimposed on the initial nano-CT scan of the native recipient patella. MATLAB was used to determine the surface height deviation between the native and donor subchondral bone surfaces. DragonFly 3-dimensional imaging software was used to measure subchondral bone step-off heights at the native-donor interface. Differences between matched and unmatched grafts were compared using a 2-way analysis of variance and the Sidak post hoc test. Results: Subchondral bone surface deviation did not differ between Wiberg matched and unmatched allografts. The step-off height was significantly greater in unmatched (1.38 ± 0.49 mm) compared with matched (1.14 ± 0.52 mm) plugs ( P = .015). The lateral quadrant step-off differed between matched (0.89 ± 0.43 mm) and unmatched (1.60 ± 0.78 mm) grafts ( P = .007). Conclusion: While unmatched Wiberg patellar osteochondral allograft implantation did not result in significantly different subchondral bone surface height deviations, there was a significant difference in the circumferential subchondral bone step-off height in the lateral quadrant. Further investigation using finite element analysis modeling will help determine the role of subchondral bone surface on shear and compression force distributions in these areas. Clinical Relevance: Given that subchondral bone stiffness and morphology play a role in cartilage health, subchondral bone congruency may play a role in graft survival. Understanding how this congruency plays a role in cartilage force distribution will help surgeons improve the long-term success of osteochondral allograft transplants.